Factors That Influence the Interest in Giving Zakat to Palestine Case Study of People in Yogyakarta - Fachri, Zein Muhammad; Sobaya, Soya (Journal of Contemporary Applied Islamic Philanthropy, 2024)
Purpose: This study aims to determine a person's interest in giving zakat to Palestine among the people in Yogyakarta by using Crow and Crow's (1987) view regarding a person's interest can grow with the presence of 3 factors, namely internal need factors, social motive factors, and emotional factors. Methodology: This study uses a quantitative approach model using probability sampling method of 100 respondents and also uses area sampling as a regional sampling technique in the Special Region of Yogyakarta. Findings: This study uses a quantitative approach model using probability sampling method of 100 respondents and also uses area sampling as a regional sampling technique in the Special Region of Yogyakarta. The results of this study indicate that charitable awareness has no partial influence on the interest in charity for Palestine, income has a partial influence on the interest in charity for Palestine, and altruism has a partial influence on the interest in charity for Palestine, and the influence of charitable awareness, income, and altruism simultaneously has an influence on the interest in charity for Palestine.